2016
DOI: 10.1159/000443119
|View full text |Cite|
|
Sign up to set email alerts
|

Huang Qi Huai Granules Induce Apoptosis in Acute Lymphoblastic Leukemia Cells through the Akt/FoxO1 Pathway

Abstract: Background/Aims: In recent years, a traditional Chinese medicine named Huang Qi Huai (HQH) has been frequently used in China for solid tumor therapy. However, the role of HQH on leukemia cells and its underlying mechanisms have not been elucidated. In this study, we investigated the effect of HQH on the proliferation and apoptosis of acute lymphoblastic leukemia (ALL) cell lines. Methods: Sup-B15 and Nalm-6 cells were treated with gradient doses of HQH for 24, 48 or 72 h. Cell viability was measured using a CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…New targets and therapy strategies against leukemia are still of intense interest [40-42]. Zinc plays dual roles in regulating cell proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…New targets and therapy strategies against leukemia are still of intense interest [40-42]. Zinc plays dual roles in regulating cell proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The following formula was used to calculate the viability ratio of ALL cells. Viability ratio=[(absorbance of experimental group-absorbance of blank group)/(absorbance of untreated group-absorbance of blank group)]×100% [23]. Each experiment was repeated for 3 times.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…Huaier has been used in TCM for ~1600 years [13]. Studies have shown that Huaier extract exhibits anti-tumor effects in a number of solid tumors [14][15][16][17][18][19][20][21][22], and according to recent reports, HQH induces apoptosis in ALL cells [23]. However, whether HQH exhibits a synergistic effect with glucocorticoids when used to treat ALL remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of the SLC7A7 gene increased the apoptosis rate of Jurkat cells. The possible signaling pathway is as follows: depletion of SLC7A7 disables transport systems that transport cationic amino acids out of the cell, increasing the amount of intracellular cationic amino acids, which can activate mTOR and contribute to apoptosis [30,31]. mTOR activation initiates the mitochondrial pathway of apoptosis and leads to phosphorylation of its downstream effector 4E-BP.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%